2016
DOI: 10.5005/jp-journals-10028-1204
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume and Platelet Distribution Width as Markers of Vascular Thrombosis in Type 2 Diabetes Mellitus

Abstract: Aims The objective of the study was to determine the mean platelet volume (MPV) and platelet distribution width (PDW) in subjects with type 2 diabetes mellitus (type 2 DM) compared to subjects without type 2 DM and their correlation with fasting blood glucose, glycosylated hemoglobin (HbA1c), and duration of type 2 DM respectively. Materials and methods A prospective analytical case—control study was conducted involving 50 subjects with type 2 DM and 50 subjects without type 2 DM. The mean and standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…They cannot be considered as a substitute for HbA1c, but in situations of financial constraints , they can be used as biomarkers for early detection of impending complication. [3,5,7,9,10,11,12,13] The results of our study prove that PDW is a more specific indicator to monitor patients with diabetes mellitus, This is in agreement with studies carried out by Vagdatli et al, Rechcnski et al, Jindal et al and Yilmaz et al [18,19,20,21]…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…They cannot be considered as a substitute for HbA1c, but in situations of financial constraints , they can be used as biomarkers for early detection of impending complication. [3,5,7,9,10,11,12,13] The results of our study prove that PDW is a more specific indicator to monitor patients with diabetes mellitus, This is in agreement with studies carried out by Vagdatli et al, Rechcnski et al, Jindal et al and Yilmaz et al [18,19,20,21]…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are comparable with the other studies. [3,4,5,11,13] Significant positive correlation was found between fasting blood sugar and PDW. [9,10,13] Kamilla et al observed a positive correlation between fasting blood sugar and PDW in diabetic patients, but Pearson correlation was not significant in controls.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations